2011
DOI: 10.1016/s1995-7645(11)60111-9
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile of brucellosis from a tertiary care center in southern India

Abstract: In countries like India, where brucellosis and tuberculosis are endemic; rapid, sensitive and highly specific diagnostic methods are required to make early diagnosis and prevent resistance as there is an overlap in therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 26 publications
2
30
0
1
Order By: Relevance
“…34.8%) have been reported in other studies. (11,13,18,21,22) In the present study, 20 patients had a negative SAT for brucellosis, according to serological diagnostic criteria (titre ≥ 1:160), during the fi rst admission. However, these patients were diagnosed with brucellosis using culture results or increasing titres.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…34.8%) have been reported in other studies. (11,13,18,21,22) In the present study, 20 patients had a negative SAT for brucellosis, according to serological diagnostic criteria (titre ≥ 1:160), during the fi rst admission. However, these patients were diagnosed with brucellosis using culture results or increasing titres.…”
Section: Discussionmentioning
confidence: 68%
“…The complaints and physical examination fi ndings at admission in other studies of patients diagnosed with brucellosis were similar to those observed in the present study. (10)(11)(12)(13)(14)(15)(16)(17)(18) The most frequent complaints among subacute and chronic brucellosis patients were back and joint pain. We believe that spondylodiscitis should be investigated in patients with back pain.…”
Section: Discussionmentioning
confidence: 99%
“…Humans are infected via the consumption of raw meat and non-pasteurised diary products that have been contaminated with brucellosis 5. Our patient had a history of consuming non-pasteurised milk and other dairy products.…”
Section: Discussionmentioning
confidence: 95%
“…Uveitis frequently occurs when the disease involves the eye. The clinical diagnosis of brucellosis requires isolation of the bacteria with a blood or tissue culture or the presence of specific antibodies via an agglutination test, complement fixation test, radioimmunoassay, or ELISA 5. Although uveitis is idiopathic with a prevalence of 30–40%, it may be comorbid with some rheumatological and infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Brucella spp. is classified as a Class B Bioterrorist agent, posing a major public health problem in many developing and developed countries [4]. …”
Section: Introductionmentioning
confidence: 99%